2022
DOI: 10.1002/hbm.26032
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiomic features for predicting the treatment response of repetitive transcranial magnetic stimulation in major neurocognitive disorder: Results from a randomized controlled trial

Abstract: Image-guided repetitive transcranial magnetic stimulation (rTMS) has shown clinical effectiveness in senior adults with co-occurring depression and cognitive impairment, yet the imaging markers for predicting the treatment response are less investigated. In this clinical trial, we examined the efficacy and sustainability of 10 Hz rTMS for the treatment of depression and cognitive impairment in major neurocognitive disorder (NCD) patients and tested the predictive values of imaging-informed radiomic features in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…Likewise, another study from 2022 focused on measuring the effectiveness of repetitive transcranial magnetic stimulation (rTMS) presented results where the basal levels of BDNF do not show differences between the control group and MDD, related neither to the severity nor to the level of cognitive deficit. In this study, only a marginal increase in BDNF levels was presented [32].…”
Section: Bdnf Levels and Treatment Response To Non-pharmacological Tr...mentioning
confidence: 50%
“…Likewise, another study from 2022 focused on measuring the effectiveness of repetitive transcranial magnetic stimulation (rTMS) presented results where the basal levels of BDNF do not show differences between the control group and MDD, related neither to the severity nor to the level of cognitive deficit. In this study, only a marginal increase in BDNF levels was presented [32].…”
Section: Bdnf Levels and Treatment Response To Non-pharmacological Tr...mentioning
confidence: 50%
“…BrainSuite is an automatic brain surface identification integrated computational platform with the updated version of cortical surface extraction, which is suitable for adults with cortical atrophy. 28 , 29 To calculate the region-specific cortical features, we followed the standard pipeline with default settings. 30 Through uploading each subject’s structural MRI data to BrainSuite, the image processing methods include a series of steps: (1) head motion correction; (2) image intensity normalization; (3) removal of the non-brain voxels; (4) segmentation of gray matter (GM), white matter (WM) and cerebrospinal fluid (CSF); (5) tessellation of GM/WM boundary, and topology correction.…”
Section: Methodsmentioning
confidence: 99%
“…The intensities in most studies were 90%, 100%, and 120% of the motor threshold. Among the various stimulation sites explored, the dorsolateral prefrontal cortex (DLPFC) emerged as a frequently targeted region across multiple studies [25,43,[51][52][53][54][55][56][57]. Additionally, other targets included the hippocampus [36,58], angular gyrus [59], precuneus [60], cerebellum [61], and regions adjacent to the temporal lobe [34,62].…”
Section: Basic Characteristicsmentioning
confidence: 99%
“…Four studies included in the analysis reported results on emotional outcomes using scales such as the Geriatric Depression Scale, Patient Health Questionnaire-9, and Cornell Scale for Depression in Dementia [36,43,52]. The findings suggest that there was no statistically significant effect on emotion compared to sham stimulation (p = 0.78, SMD = 0.07, 95%CI = -0.40-0.53) (see Fig.…”
Section: Effects Of Rtms On Emotionmentioning
confidence: 99%